Mosby's physical examination video series - Seidel, Henry M.; Ball, Jane W.; Dains, Joyce E.; Benedict, G. William; Elsevier Science (Firm) ([St. Louis, Mo.] : Mosby Elsevier, 2010)
Eighteen full-motion videos provide a visual presentation on how to perform a complete and effective physical examination. Each video focuses on the techniques of the examination, how the examiner interacts with the patient, and how the examiner proceeds through the examination process.
1. Neurologic system: mental status and cranial nerves -- 2. Skin, hair and nails -- 3. Head, and neck and lymphatic -- 4. Eyes -- 5. Ears, nose, and throat -- 6. Chest and lungs -- 7. Heart -- 8. Blood vessels -- 9. Breasts and axillae -- 10. Abdomen -- 11. Female genitalia and rectum -- 12. Male genitalia, rectum, and prostate -- 13. Musculoskeletal system -- 14. Neurologic system: motor and sensory functions and reflexes -- 15. Putting it all together -- 16. Effective communication and interviewing skills -- 17. Physical examination of the hospitalized patient -- 18. Putting it all together: physical examination of the child.
Developed in conjunction with Mosby's Guide to Physical Examination by Seidel, Ball, Dains, and Benedict.
Networkable DVD videos 1-18.
Keywords: Physical Examination -- methods